Utilização de um Sistema de Informações Geográficas para o Planejamento Ambiental em Rio Grande, RS - Brasil - TAGLIANI, CARLOS RONEY ARMANINI (Pesquisas em Geociências, 2000)
The social, economics and environmental problems that arise by the fast and inadequate occupation of the coastal zones have required faster decisions and belter rational use of the public administration resources. This work shows the utilization of Geographical Information System IDRISI to environmental planning of Rio Grande county, southern Brazil. Based on digital thematic maps of geology, soils, vegetation. urban sites, legal protection areas and previous knowledge about the ecosystem under consideration, the more appropriated areas for agricultural activities, pine and eucalyptus forestry and waste disposal were mapped. The suitable environmental conditions and the technical and/or environmental restrictions were analysed for each item and then modelled in the computer using the analytical tools of the software. Furthermore, the legal protection areas were classified in conservation and preservation categories according to their environmental characteristics. The results demonstrated the potentiality and feasibility of a Geographical Information System as a powerful tool for organi13tion, analysis and decision making on municipal planning.